Mean Convergence Time of Inhomogeneous Genetic Algorithm with Elitism. (2nd August 2016) - Cruz, Juan Alberto Rojas; Diniz, Iesus C.
ABSTRACT: The theoretical study of a genetic algorithm (GA) has focused mainly on establishing its convergence in probability and almost always to the global optimum. In this article, we establishsufficient conditions for the finiteness of convergence mean time of the genetic algorithm with elitism. We obtain bounds for the probability of convergence to the global optimum in the first n iterations as a by-product.